Prūsų kalbos veiksmažodžių struktūros ypatumai - Kaukienė, Audronė (Baltistica, 1998)
PECULIARITIES OF VERB STRUCTURE IN OLD PRUSSIAN Two types of verbs with a suffix variation have been reconstructed on the basis of Old Prussian catechisms. Verbs of type 1 have the suffix -ī- in the Infinitive and its derivatives (the vowel ī in the dialects of the catechisms is slightly diphthongized, pronounced as eī and recorded as ī, ij, ei, i), and the suffixes -ē- and -ā- in the Present and Past tenses, e.g. billīt, billītwei ‘to speak’, billīton ‘is said’, bille ‘I speak, you speak, he speaks’, billē / billā, billa ‘speaks’, billēmai ‘we speak’, billai ‘I spoke’, billa, byla, bela, billāts, belats, bilats, bylaczt / billē ‘he spoke’. Verbs of this type can correspond to verb forms with different structures in East Baltic languages or have no correspondences at all. In the linguistic literature the suffix -ī- of the Infinitive is usually presented as being derived from *-ē- on the basis of the theoretically reconstructed thematic stems of the Present and Past tenses. Yet the existing materials do not support this kind of reconstruction, Verbs of type 2 have the suffix *-ē- in the Infinitive and its derivatives (the vowel ē in the dialects of the catechisms became narrower and was pronounced almost as ī), and the suffix -ī̆- at the end of the Present tense stem (the Past tense forms have not been recorded); e.g. turīt, turrit, turrītwei, turrettwey, turryetwei (*tur-ē-) ‘to have’, turri ‘I have’, tur, turri, turei ‘you have’, turri, turei, turret,ture ‘he has, they have’, turrimai ‘we have’, turriti ‘you have’. In East Baltic languages their equivalents are i-stem verbs with the suffix -ē- in the Infinitive. Type 1 is very copious and productive, while type 2 ought to be considered a relic. Yet the dominance of type 1 should be accounted for not by phonological, but rather by morphological reasons, as in live Old Prussian *ē > ī and *i > eī could not have merged.